2021
DOI: 10.3390/cancers13143601
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome and Risk Factors of Red Blood Cell Transfusion in Patients Undergoing Elective Primary Meningioma Resection

Abstract: Transfusion of red blood cells (RBC) in patients undergoing major elective cranial surgery is associated with increased morbidity, mortality and prolonged hospital length of stay (LOS). This retrospective single center study aims to identify the clinical outcome of RBC transfusions on skull base and non-skull base meningioma patients including the identification of risk factors for RBC transfusion. Between October 2009 and October 2016, 423 patients underwent primary meningioma resection. Of these, 68 (16.1%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…30 Additionally, previous studies reported that skullbased surgery and meningioma are potential factors linked with blood transfusion. 8,9 These were in concordance with our findings which shows that intraosseous/skull-based tumor and meningioma were associated with both intraoperative transfusion and massive blood loss. Although meningioma is a benign tumor, hypervascularity and numerous feeding vessels are common findings of this tumor.…”
Section: Discussionsupporting
confidence: 91%
“…30 Additionally, previous studies reported that skullbased surgery and meningioma are potential factors linked with blood transfusion. 8,9 These were in concordance with our findings which shows that intraosseous/skull-based tumor and meningioma were associated with both intraoperative transfusion and massive blood loss. Although meningioma is a benign tumor, hypervascularity and numerous feeding vessels are common findings of this tumor.…”
Section: Discussionsupporting
confidence: 91%
“…However, in addition to having a variable cost per unit transfused, blood transfusion has been documented to be linked to a greater risk of developing wound infections, pulmonary embolism, acute lung injury and prolonged hospital length of stay (LOS) [44,45]. Neef et al [46] indicated that transfusion was a risk factor after elective primary meningioma resection, which was consistent with our result. The transfusion rate can be ranged from 20.0 to 35% in previous studies [47][48][49].…”
Section: Discussionsupporting
confidence: 90%
“…Ten studies reported on intracranial tumour surgery 940–949 . A retrospective observational study including 8924 patients reported an RBC transfusion rate of 7% with an increased morbidity and mortality 950 .…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies reported on intracranial tumour surgery. [940][941][942][943][944][945][946][947][948][949] A retrospective observational study including 8924 patients reported an RBC transfusion rate of 7% with an increased morbidity and mortality. 950 Other studies demonstrated an incidence of peri-operative bleeding resulting in RBC transfusion between 2.4 and 7%.…”
Section: Intracranial Surgerymentioning
confidence: 99%
See 1 more Smart Citation